(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
Sport permeates all levels of modern society, exerting a wide impact on the main spheres of society. It influences national relations, business life, social status, shapes fashion, ethical values, and people’s way of life. Every profession has its own functions and techniques, as well as definitions and concepts specific to a particular profession.